Facilitated Loading of Horizontal Gels Using a Capillary Comb Loader. (April 2003) - Thompson, J.; Pugh, T.; Guggenheimer, K.; Safarpour, A.; Christie, A.; Pel, J.; Chow, S.; Marziali, A.
Manual loading of samples into horizontal gels, such as the agarose gels commonly used for DNA fragment sizing and quantification, is laborious and prone to errors. Manual-loading times for highthroughput gels can reach 10 min/gel, and human error can result in incorrect identification of samples because of reverse loading or other errors in the loading process. To reduce gel-loading times and to improve reliability, a novel comb has been developed that uses glass capillaries and hydrostatic pressure to simplify sample loading from microplates. Accurate sample metering is ensured by the uniform length and volume of the capillaries. The loaded comb is placed in the gel boat over a pre-cast agarose gel, and buffer is added to a reservoir at the top of the comb. Once the buffer rises over the ends of the capillaries, the samples are pushed into the wells by hydrostatic pressure. This technique was successfully demonstrated for a 24-lane comb. This capillary comb loader reduces loading time, maintains well-to-well uniformity, and retains the same geometry and appearance of manually loaded bands, making this loading method compatible with existing downstream processes and software for subsequent analysis of the gel image.